Filmes antioxidantes comestíveis de celulose bacteriana e hidrolisado de gelatina de pele de pescado - Lima, Helder Levi Silva (2018)
Edible polymers, natural compounds and nanotechnology are often associated in studies that aim to obtain high performance bioactive films, an innovative technology for food preservation and food quality/safety improvement. Bacterial cellulose (BC), a natural nanostructured polymer, exhibit unique properties and applicability in the food industry. BC can be obtained by bioconvertion of nutrients from agroindustry residues or by-products, such as cashew apple juice, after cultivation of the Komagaetaibacter strain. Antioxidant peptides, a class of bioactive compounds, can be obtained from Tilapia skin (Oreochromisniloticus), a fish species of great commercial expressiveness. Active peptides are potential alternatives to the synthetic antioxidants for foods, which are related to deleterious effects on the human health. In this work, antioxidant films based on nanofibrilated bacterial cellulose (BCNF) and Tilapia skin gelatinehydrolyzate (HA) were developed and characterized. When evaluating the effect of the HA amount on antioxidant activity (Aox), the film containing 60% of HA showed the best result. The film with 40% of HA, 40% of BCNF and 20% of sorbitol (HS40HA40S20) exhibited better performance to Aox, solubility, thermal stability and Young modulus (E) when compared to the same film plasticized with glycerol. The use of CBNF from alternative source (cashew juice fermentation) did not affect the Aa, color, contact angle, transparency, water vapor permeability and Young's modulus of CM40HA40S20 film composed by CBNF from alternative medium (CM). The alternative BCNF improves the tensile strength, elongation at break, thermal stability and crystallinity degree of CM40HA40S20 film. Neither component of antioxidant film, HS40HA40S20 or CM40HA40S20, show cytotoxicity in assay with intestinal epithelial human cells (in vitro) suggesting an indication of safety for edible films applications. The release of protein from antioxidant films, containing different amounts of HA, occurs quickly in different fluids, with a predominance of non-Fickian transport mechanisms.